LABORATORY-DIAGNOSTIC METHODS OF HEMORRHAGIC VASCULITIS DISEASE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Hemorrhagic vasculitis, also known as Henoch-Schönlein purpura (HSP), is a small vessel vasculitis that affects the skin, joints, gastrointestinal system, and kidneys. Early and accurate diagnosis is essential for the effective management of the disease. This article reviews various laboratory and diagnostic methods, including biochemical, immunological, and histological techniques, that are critical for identifying the disease and assessing its progression. The goal is to highlight diagnostic markers and emerging technologies that aid in the prompt detection of hemorrhagic vasculitis.